High-frequency power conversion for photovoltaic module applications - Sergentanis, Grigorios (2024)
As world governments focus on transitioning to renewable energy production, power electronics are a mandatory tool in facilitating this transition. Power electronic converters are needed in all types of renewable energy production, whether that is wind, solar, geothermal, or wave energy.